Diversification of traditional paddy field impacts target species in weed seedbank - Rubia Dominschek (Revista Ciência Agronômica, 2022)
ABSTRACT Weed competition is a challenge to rice monocropping growers in the context of herbicide resistant weeds and difficult weeds to manage using chemical control. Diversifying crop rotations through integrated crop-livestock systems (ICLS) can be an alternative to face this challenge. As weed seedbank reflects management practices, this study aimed to assess the impact of a traditional paddy field and four lowland ICLS on the weed seedbank, in a long-term ICLS experiment located in Cristal, RS, Brazil. Treatments consisted of five cropping systems: T1 - rice monocropping; T2 - rice-beef cattle integration; T3 - soybean-rice-beef cattle integration; T4 - Sudan grass-soybean-maize-rice-beef cattle integration; and T5 - rice-beef cattle integration in cultivated and natural grassland. The seedbank was assessed in the fourth experimental year, Oct-2016, at three soil depths (0-5; 5-10 and 10-20 cm). In a mid-term temporal scale, the diversification of paddy field through ICLS did not affect weed seedbank size. However, seeds in T1 were equally distributed along the soil profile, in contrast to the other cropping systems, where weed seeds accumulated in the 0-5 cm depth. Lowland ICLS designs that comprises the integration of summer crops with grazing winter cover crops decrease the proportion of Cyperaceae weed species in the topsoil seedbank. The depletion of weedy rice seedbank is more pronounced in lowland ICLS designs that integrates different summer crop in rotation with grazing cover crops.